Outcome of internal fixation of posterior cruciate ligament avulsion injury fixation - Gupta, Hemant Kumar (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: The posterior cruciate ligament (PCL) avulsion form tibial attachment can be managed by fixation with many techniques, in this study, open reduction and internal fixation with canulated cancellous screws through posterior approach done and the radiological union and functional outcome was evaluated. Methods: Total 24 cases of PCL avulsion managed with fixation through posterior approach with cannulated cancellous screws over a period from February 5, 2017 to June 30, 2024 with the follow-up for 12 months was performed. The final outcome was evaluated on the basis of radiological union and Lysholm score. Results: In this study, the mean age was 33.91 years, male (75%) and female (25%) with most injuries on right side (79.16%). At the final follow-up for the mean duration of 13.1 months (SD=1.21 months) in all patients, fracture was united and all patient had full extension and mean flexion 1250± 7.50. The functional outcome assessed by the Lysholm scoring system was excellent in 17 patients, good in six patients and fair in one patient (average Lysholm score was 97±7.6). Around five patients had residual pain and swelling in the joint and six the patients had mild (grade 1) instability tested clinically using the drawer test. Conclusions: Fixation of PCL avulsion was safely done with posterior approach and the results were excellent in terms of radiological union and function of the knee.